2014
DOI: 10.1071/eg12085
|View full text |Cite
|
Sign up to set email alerts
|

Pre-stack depth migration for improved imaging under seafloor canyons: 2D case study of Browse Basin, Australia

Abstract: In the Browse Basin, as in many areas of the world, complex seafloor topography can cause problems with seismic imaging. This is related to complex ray paths, and sharp lateral changes in velocity. This paper compares ways in which 2D Kirchhoff imaging can be improved below seafloor canyons, using both time and depth domain processing.In the time domain, to improve on standard pre-stack time migration (PSTM) we apply removable seafloor static time shifts in order to reduce the push down effect under seafloor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Our migration of the data shows that the artifacts produced by these prism waves can appear to be geological. This is most evident in Figure 5, in this case prism waves produce low frequency energy both above and below the real canyon floor (at 500 ms and 830 ms), this is consistent with the effect seen in data in Debenham and Westlake (2013) Figure 4a. With some more complex layering these artifacts could easily be misinterpreted to be real structure.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our migration of the data shows that the artifacts produced by these prism waves can appear to be geological. This is most evident in Figure 5, in this case prism waves produce low frequency energy both above and below the real canyon floor (at 500 ms and 830 ms), this is consistent with the effect seen in data in Debenham and Westlake (2013) Figure 4a. With some more complex layering these artifacts could easily be misinterpreted to be real structure.…”
Section: Discussionsupporting
confidence: 87%
“…This is a significant problem for the oil and gas industry as many targets lie beneath or proximal to these continental shelf breaks. Bisley and MacNeill (2008), Debenham and Westlake (2013) demonstrated that such seafloor canyons present particular challenges on the North-West shelf (NWS) in Western Australia. Neglecting these wavefield complexities can result in inaccurate velocity models, significant imaging errors, misleading amplitudes and uncertain interpretations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeks and Lumley (2015) pointed out that multiple paths of prism waves are usually generated by the canyons, even at short offsets. Prism wave energy becomes stronger in narrow and deep canyons and creates shadow events in stacked images and CDP gathers (Deeks and Lumley, 2015;Debenham and Westlake, 2014). Confidence in picking proper RMO and geological events is low in the presence of prism waves.…”
Section: Introductionmentioning
confidence: 99%